Амедео Модильяни - Виленкин Виталий Яковлевич (Жизнь в искусстве, 1989)
Экземпляры: ХР (20180706) / Инвентарный номер: 25162 / Цена: 2.70 / Сис.шифр: 85.143(3) / Авт.знак: В 44 / ГРНТИ: 18 / ББК: 85.143(3)